2013
DOI: 10.1136/gutjnl-2013-305639
|View full text |Cite
|
Sign up to set email alerts
|

A validated tool to predict colorectal neoplasia and inform screening choice for asymptomatic subjects

Abstract: The scoring system based on age, gender, smoking, family history, Body Mass Index and self-reported diabetes is useful in predicting the risk of colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 34 publications
3
93
2
Order By: Relevance
“…A majority (n=35) of models include variables obtained through a questionnaire [18,19,21,22,23,24,25,26,27,28,30,33,36,37,38,39,40,41,42,43,44,45,46,49,50,51,53,54]. The questionnaires range from those with only one or two simple questions to those with detailed questions on factors such as diet, physical activity, alcohol and smoking habits and past medical facts.…”
Section: Development Of the Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority (n=35) of models include variables obtained through a questionnaire [18,19,21,22,23,24,25,26,27,28,30,33,36,37,38,39,40,41,42,43,44,45,46,49,50,51,53,54]. The questionnaires range from those with only one or two simple questions to those with detailed questions on factors such as diet, physical activity, alcohol and smoking habits and past medical facts.…”
Section: Development Of the Modelsmentioning
confidence: 99%
“…A majority of the studies have used multiple logistic regression to identify the risk predictors [16,27,28,30,33,34,35,41,43,47,50,52] followed by the allocation of the risk points, based on the values of beta-coefficients [14,15,18,21,23,24,36,37,39,45,46,48]. Fourteen models have incorporated Cox proportional hazards regression to develop the risk model and the score [17,19,20,22,38,40].…”
Section: Development Of the Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…More details could be found elsewhere. [19][20][21] We assumed the rate of compliance with colonoscopy was 98.9%. The overall age-adjusted rate of polypectomy was 43.5% (50.3% for male and 37.3% for female), cumulative over 20 years when the screening participants join the program at 50 years till 70-year old.…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…6 Other validated risk scores have been constructed using similar methods and have potential for use in clinical practice. 7,8 Yeoh et al 5 also identified some issues related to the application of the APCS score. The objective of this commentary is to discuss the potential challenges and perspectives for future research into risk-based CRC screening.…”
mentioning
confidence: 99%